ANALISIS KETERAMPILAN BERBICARA MELALUI PANTUN DI SEKOLAH DASAR - AYU SARADINA LAROSA; ROSSI ISKANDAR (Universitas Trilogi, 2022)
Speaking skill is the skill of producing a stream of articulation sound systems that are used to appreciate, and convey ideas, desires, feelings, or desires in accordance with the context being faced by the reader. The method used in this research is a descriptive qualitative using poems as a medium for observation. The subjects of this study were teachers and students of grade 5 elementary school at SDN Pengadegan 07 Pagi. Data was obtained from observations, interviews, and questionnaires. The data obtained were checked for data, data encoding, clarification, and correction, and presented properly. The analysis technique used is based on the theory of Miles and Huberman which includes (1) data collection, (2) data reduction, (3) data display, (4) conclusion/verification. The results of this study are speaking skills at SDN Pengadegan 07 Pagi through poem students can convey the main idea well, the majority of children have given the main idea but articulation and intonation are low. The advantages of speaking skills through rhymes are that students can convey main ideas more creatively, speak loudly, and straightforwardly, have a good tempo, and are easy to understand. Deficiency of speaking skills through rhymes is a minimum of reaction from listeners because online, the reading tone and tempo are monotonous, and there are students who have poor intonation.